Developing an E-Busy Big Book Based on the CIRC Model to Improve Elementary Students’ Understanding of New Vocabulary - Tazkia Fathia Zuhda; Panca Dewi Purwati (JOLLT Journal of Languages and Language Teaching, 2026)
This study aims to develop an E-Busy Big Book based on the Cooperative Integrated Reading and Composition (CIRC) model to improve the understanding of new vocabulary among second-grade elementary students. Using a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate), the study involved 6 students for a small-scale trial and 18 second-grade students for a large-scale trial selected through purposive sampling from SD Negeri Bentul and SD Negeri 1 Kebasen. Data were collected through expert validation questionnaires, pre-tests, post-tests, and teacher–student response forms. Quantitative data were analyzed descriptively to determine media feasibility and learning outcome improvements, while qualitative data captured user responses. The media achieved a feasibility score of 91%, categorized as “very feasible.” Learning outcome analysis showed a significant increase in vocabulary understanding, with the average score rising from 66.10 (pre-test) to 84.80 (post-test). Students demonstrated increased motivation and engagement, while teachers noted the practicality and effectiveness of the media. The study highlights the potential of integrating CIRC-based digital Big Book media to support vocabulary learning in early-grade elementary settings and offers practical implications for improving literacy instruction in Indonesian primary schools.